Efficacy of four selective Trichoderma isolates as plant growth promoters in two peanut varieties - Kamaruzzaman, M.; Rahman, M. M.; Islam, M. S.; Ahmad, M. U. (International Journal of Biological Research, 2016)
Trichoderma species are generally used as potential bio control agents against wide range of plant pathogenic fungi and some strains are reported to produce metabolites that enhance plant growth. In the current study we evaluated the four Trichoderma isolates viz. T. harzianum (ST5), T. viride (ST6), T. virens (ST7) and T. atroviride (ST9) including a control were tested as seed treatment against to find out a potential growth-promoter of Peanut. T. harzianum (ST5) gave maximum length and weight of shoot, weight of roots with pods, weight of pods and number of nodules per plant. T. viride (ST6) showed higher plant growth, nodulation and yield compared to T. virens (ST7) and T. atroviride (ST9). Minimum growth, yield and nodulation were observed with control treatment.